The validity of the German version of the Health of the Nation Outcome Scales (HoNOS-D): a clinician-rating for the differential assessment of the severity of mental disorders - Andreas, Sylke; Harfst, Timo; Rabung, Sven; Mestel, Robert; Schauenburg, Henning; Hausberg, Maria; Kawski, Stephan; Koch, Uwe; Schulz, Holger (International journal of methods in psychiatric research, 2010)
The Health of the Nation Outcome Scales (HoNOS) is an internationally-established clinician-rating instrument for the differential assessment of the severity of patients with mental disorders. The aim of this study was to examine the validity of the German version of the HoNOS (HoNOS-D). Evaluation of validity, including factor validity, convergent and discriminant validity and sensitivity to change, was conducted on a large, virtually representative, clinical sample of patients with mental disorders in inpatient psychotherapy (Study 1, N = 3169). Additional assessment of criterion-based validity was completed using another clinical sample of patients with mental disorders (Study 2, N = 55). Although factor validity of the HoNOS-D and its total score could not be confirmed as expected, the majority of single items of the HoNOS-D proved to be valid in terms of convergent validity, criterion-based validity and sensitivity to change. Hence, single items, rather than the total score of the HoNOS-D, can be recommended for obtaining a picture of the impairment of patients with mental disorders in the clinical setting.